Genome-wide identification of the MATE gene family and functional characterization of PbrMATE9 related to anthocyanin in pear - Jiawen Sheng; Xuening Chen; Bobo Song; Hainan Liu; Jiaming Li; Runze Wang; Jun Wu (Horticultural Plant Journal, 2023)
Plant multidrug and toxic compound extrusion (MATE) genes play an important role in the process of detoxification, plant morphogenesis, and anthocyanin accumulation. However, whether the MATE gene family functions in pear peel coloration is still unknown. To evaluate and identify the MATE gene family members which are involving in anthocyanin accumulation and coloration in pear. In this study, 85 MATE genes were identified in the reference pear genome of ‘Dangshansuli’ through genome-wide identification. Based on gene structure and phylogenetic tree analysis, the MATE family was divided into five subfamilies. RNA sequencing and quantitative real-time polymerase chain reaction (qRT-PCR) indicated that the expression patterns of PbrMATEs were tissue-specific. 28.24% (24) of PbrMATE genes were expressed in the fruits, and 44.71% (38) of PbrMATE genes were expressed in the leaves. Additionally, we found that the expression levels of PbrMATE9, PbrMATE26, PbrMATE50, and PbrMATE69 in debagged fruits with red peel were significantly higher than those in bagged fruits without red peel, according to our bagging/debagging treatment of ‘Mantianhong’. The expression pattern of PbrMATE9 was consistent with the variation trend in anthocyanin content, suggesting that it might play an important role in anthocyanin accumulation in response to light exposure. Subcellular localization showed that PbrMATE9 was a membrane protein. More strikingly, the transient overexpression of PbrMATE9 promoted anthocyanin accumulation in the peel of pear, and the expression of structural genes (PbrCHI, PbrANS, PbrDFR, and PbrUFGT) in the anthocyanin biosynthesis pathway also increased significantly. Through co-expression network analysis, the transcription factors were identified, such as WRKY, COL, GATA, and BBX, which might be involved in the regulation of PbrMATE9. The study has enriched the genetic resources and improved the understanding of the regulation network of anthocyanin accumulation in pear.